Images of Revolution: An American Photographer in Petrograd, 1917 - Mould, David H. (Journal of Russian American Studies, 2017)
Photographer Donald Thompson arrived in Petrograd on the eve of the February Revolution in 1917. Over the next six months, he photographed demonstrations and street-fighting, was caught in crossfire, arrested, and thrown in jail. He traveled to Moscow and the front lines, and photographed Tsar Nicolas II, political and military leaders, and prominent foreign visitors. He witnessed the power struggle between the Provisional Government and the Petrograd Soviet, and the breakdown of discipline in the army. Donald Thompson in Russia, a compilation of letters to his wife with photos, published in 1918, outlines his conspiracy thesis that “German intrigue, working among the unthinking masses, has brought Russia to her present woeful condition.”